Pelaksanaan Budaya Keselamatan Pasien pada Masa Pandemi Covid-19 di Rumah Sakit Umum Daerah Bima - Muhtar Muhtar; Aniharyati Aniharyati; Ahmad Ahmad (Bima Nursing Journal, 2020)
Patient safety is an indicator of the quality of health service facilities, therefore the hospital always strives to improve the quality of service by providing safe and quality care and building a culture of patient safety even during crisis situations such as the Covid-19 pandemic. Aimed at knowing the description of the implementation of patient safety culture in RSUD Bima, this study used a descriptive observational design with a cross-sectional approach, respondents were taken by simple random sampling, data collection used the Hospital Survey on Patient Safety Culture (HSOPSC) questionnaire. In general, the implementation of patient safety culture in most dimensions has been perceived positively by more than 80% of respondents. Meanwhile, the lowest positive perception on the response dimension did not blame the error (47.5%), staff management (57.6%) and the frequency of reporting events / incidents (58.5%). The investigators recommend continuing to improve the patient safety culture with special attention paid to the low mean dimensions to refine and strengthen these dimensions